Antagonistic anti-LILRB1 monoclonal antibody regulates antitumor functions of natural killer cells. Issue 2 (7th August 2020) - Chen, Heyu; Chen, Yuanzhi; Deng, Mi; John, Samuel; Gui, Xun; Kansagra, Ankit; Chen, Weina; Kim, Jaehyup; Lewis, Cheryl; Wu, Guojin; Xie, Jingjing; Zhang, Lingbo; et al.
Abstract : Background: Current immune checkpoint blockade strategies have been successful in treating certain types of solid cancer. However, checkpoint blockade monotherapies have not been successful against most hematological malignancies including multiple myeloma and leukemia. There is an urgent need to identify new targets for development of cancer immunotherapy. LILRB1, an immunoreceptor tyrosine-based inhibitory motif-containing receptor, is widely expressed on human immune cells, including B cells, monocytes and macrophages, dendritic cells and subsets of natural killer (NK) cells and T cells. The ligands of LILRB1, such as major histocompatibility complex (MHC) class I molecules, activate LILRB1 and transduce a suppressive signal, which inhibits the immune responses. However, it is not clear whether LILRB1 blockade can be effectively used for cancer treatment. Methods: First, we measured the LILRB1 expression on NK cells from cancer patients to determine whether LILRB1 upregulated on NK cells from patients with cancer, compared with NK cells from healthy donors. Then, we developed specific antagonistic anti-LILRB1 monoclonal antibodies and studied the effects of LILRB1 blockade on the antitumor immune function of NK cells, especially in multiple myeloma models, in vitro and in vivo xenograft model using non-obese diabetic (NOD)-SCID interleukin-2Rγ-null mice. Results: We demonstrate that percentage of LILRB1 + NK cells is significantly higher in patients with persistent multiple myeloma after treatment than that in healthy donors. Further, the percentage of LILRB1 + NK cells is also significantly higher in patients with late-stage prostate cancer than that in healthy donors. Significantly, we showed that LILRB1 blockade by our antagonistic LILRB1 antibody increased the tumoricidal activity of NK cells against several types of cancer cells, including multiple myeloma, leukemia, lymphoma and solid tumors, in vitro and in vivo . Conclusions: Our results indicate that blocking LILRB1 signaling on immune effector cells such as NK cells may represent a novel strategy for the development of anticancer immunotherapy.